Acupuncture for Pain and Function in Patients with Nonspecific Low Back Pain: Study Protocol for an Up-to-Date Systematic Review and Meta-Analysis - Li Y; Liu Y; Zhang L; Zhai M; Li L; Yuan S; Li Y (Journal of Pain Research, 2022)
Yunxia Li,1,2 Yangyang Liu,1,2 Lihui Zhang,1,2 Mimi Zhai,2 Li Li,2 Sue Yuan,1 Yamin Li3 1Teaching and Research Section of Clinical Nursing, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China; 2Xiangya Nursing School, Central South University, Changsha, Hunan, 410013, People’s Republic of China; 3Teaching and Research Section of Clinical Nursing, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of ChinaCorrespondence: Sue Yuan, Teaching and Research Section of Clinical Nursing, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China, Email ldyse2018@csu.edu.cn Yamin Li, Teaching and Research Section of Clinical Nursing, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China, Email aminny@csu.edu.cnAim: To assess the pain and function of acupuncture in patients with nonspecific low back pain (NSLBP).Design: This is a study protocol for an upcoming, updated systematic review and meta-analysis. We have registered on the PROSPERO platform, and the registration number is CRD42020149647.Methods: We will identify studies in seven English databases, including Web of Science, Cochrane Library, CINAHL, Physiotherapy Evidence Database, Medline, Embase, and Scopus, and in four Chinese databases, including China National Knowledge Infrastructure (CNKI), China Biology Medicine disc (CBMdisc), Wanfang Database, and VIP database. We will also manually search key journals about acupuncture, the references of identified relevant trials, and the Clinical Trials Registry Platform. Different search strategies of Medical Subject Headings (MeSH) and non-MeSH terms will be applied alone or integrated. We will evaluate methodological quality by adopting Cochrane’s risk of bias criteria and perform a meta-analysis using RevMan V.5.4 software.Results: This study’s results will be reported according to the PRISMA checklist and presented at an authoritative scientific conference or an authoritative scientific journal.Keywords: acupuncture, nonspecific low back pain, protocol, update, meta-analysis